(untitled) (Comparative Professional Pedagogy, 2021)
The study highlights three types of international students’ adaptation: academic, social and cultural. The most typical challenges in each adaptation are identified and described. Academic challenges include lack of language proficiency, different education values, interaction with the university faculty, staff and mates. Social issues for international students are living on- or off-campus, initial difficulties, independence and loneliness, relationship with domestic students and involving them into university life. Culturally, international students face the following challenges: culture shock, the lack of culture wellness. Thus, as demonstrated in this study, having a better understanding of these students’ challenges, university faculty and staff can recognize students’ needs and effectively offer supportive services. The university needs to be prepared to meet students not only academically but also socially and culturally. This study also describes the priorities in Canadian international education strategy that makes Canada one of the world’s top learning destinations. Federal and provincial governments Canada demonstrate their increasing interest in the global education market. It is reflected in the well-designed Canada’s International Strategy for 2014–2019. According to it, there are three key objectives before Canadian educational system: to encourage Canadian students to gain new skills through using opportunities to study and work abroad in key global markets, especially Asia; to diversify the range of countries international students come from to Canada, as well as their fields, levels of study, and location of study within Canada; increase support for Canadian educational institutions to help grow their export services and explore new opportunities abroad.